Competences of Professors: a competitive advantage - Hanashiro, Darcy Mitiko Mori; Nassif, Vânia Maria Jorge (Review of Business Management, 2007)
The objective of this research was to verify if the Human Resources function in five Brazilian private universities stimulates the development and the exercise of the professor’s competences needed to raise their competitiveness. A qualitative research was conducted interviewing top management and Human Resources professionals of these universities. Another quantitative research was carried out using a self applied and closed questionnaire answered by 282 professors. A factor analysis identified 12 factors of professor’s competences that are viewed fundamental to exercise teacher’s function. Results revealed the professors recognize what are the competencies needed; however, the universities do not realize Human Resources actions facilitating them to develop these competences, promoting competitiveness in the academic market. Key-words: Professor’s competences. University competitiveness. Private university.